쌀면전용 고아밀로스 중생 통일형 벼 ‘새미면’ - 조준현(Jun-Hyeon Cho); 이종희(Jong-Hee Lee); 박노봉(No-Bong Park); 손영보(Young-Bo Son); 오성환(Sung-Hwan Oh); 한상익(Sang-Ik Han); 송유천(You-Chun Song); 서우덕(Woo-Duck Seo); 박동수(Dong-Soo Park); 남민희(Min-Hee Nam); 이지윤(Ji-Yoon Lee) (Korean journal of breeding, 2018)
Saemimyeon, a Tongil type, medium-late maturing rice variety, is especially used for preparing rice noodles. Its high amylose content was developed to fit market demands and to be affordable for rice processing industries. One of the high yielding lines, Milyang181 (Hanareum), was used in the final three-way cross of IR50*2/YR18241-B-B-115-1-1 for yield improvement and cultivation stabilization, including disease resistance. YR24235-10-1-3, a high yielding and compact plant type, was selected and named Milyang278 after yield test at NICS (RDA, Miryang) in 2010. It was subjected to regional yield test at six sites in the middle and southern plain areas of South Korea. Saemimyeon heading occurs on August 12 and is a mid-late maturing cultivar, with resistance to leaf blast, rice stripe virus, and bacterial blight (K1-K3a), but it is susceptible to major diseases and insect pest infestation. Saemimyeon showed a high amylose content of 26.7%, with a relatively low KOH digestion value of 3.5, which are key factors in rice noodles and pasta processing. In the local adaptability tests, the yield of Saemimyeon was 7.08 MT/ha—an increase of approximately 106% compared to that of Dasan. Thus, Saemimyeon is suitable for cultivation in the southern and middle plain areas of South Korea. KCI Citation Count: 6